The Serotonin Receptor Subtype 5b Specifically Interacts with Serotonin Receptor Subtype 1A - Niebert, Sabine; van Belle, Gijsbert J.; Vogelgesang, Steffen; Manzke, Till; Niebert, Marcus (Frontiers in Molecular Neuroscience, 2017)
Previously, we described the dysregulation of serotonin receptor subtype 5b (5-ht5b) in a mouse model of Rett syndrome (RTT). 5-ht5b has not been extensively studied, so we set out to characterize it in more detail. Unlike common cell surface receptors, 5-ht5b displays no membrane expression, while receptor clusters are located in endosomes. This unusual subcellular localization is at least in part controlled by glycosylation of the N-terminus, with 5-ht5b possessing fewer glycosylation sites than related receptors. We analyzed whether the localization to endosomes has any functional relevance and found that 5-ht5b receptors can specifically interact with 5-HT1A receptors and retain them in endosomal compartments. This interaction reduces 5-HT1A surface expression and is mediated by interactions between the fourth and fifth trans-membrane domain. This possibly presents a mechanism by which 5-ht5b receptors regulate the activity the other serotonin receptor.